Glycan repositioning of influenza hemagglutinin stem facilitates the elicitation of protective cross-group antibody responses - Boyoglu-Barnum, Seyhan; Hutchinson, Geoffrey B.; Boyington, Jeffrey C.; Moin, Syed M.; Gillespie, Rebecca A.; Tsybovsky, Yaroslav; Stephens, Tyler; Vaile, John R.; Lederhofer, Julia; Corbett, Kizzmekia S.; Fisher, Brian E.; Yassine, Hadi M.; et al. (Nature communications, 2020)
The conserved hemagglutinin (HA) stem has been a focus of universal influenza vaccine efforts. Influenza A group 1 HA stem-nanoparticles have been demonstrated to confer heterosubtypic protection in animals; however, the protection does not extend to group 2 viruses, due in part to differences in glycosylation between group 1 and 2 stems. Here, we show that introducing the group 2 glycan at Asn38 HA1 to a group 1 stem-nanoparticle (gN38 variant) based on A/New Caledonia/20/99 (H1N1) broadens antibody responses to cross-react with group 2 HAs. Immunoglobulins elicited by the gN38 variant provide complete protection against group 2 H7N9 virus infection, while the variant loses protection against a group 1 H5N1 virus. The N38 HA1 glycan thus is pivotal in directing antibody responses by controlling access to group-determining stem epitopes. Precise targeting of stem-directed antibody responses to the site of vulnerability by glycan repositioning may be a step towards achieving cross-group influenza protection. Influenza virus hemagglutinin (HA) stem between group 1 and 2 viruses has different glycosylation patterns, likely hampering cross-group protection. Here, Boyoglu-Barnum et al. show that introducing a group 2 glycan into a group 1 stem nanoparticle vaccine broadens antibody responses in mice to cross-react with group 2 HAs.